Hepatosplenic Sarcoidosis: Contrast-Enhanced Ultrasound Findings and Implications for Clinical Practice. (18th August 2014) - Tana, Claudio; Dietrich, Christoph F.; Schiavone, Cosima
Abstract : Sarcoidosis is a complex granulomatous disease that affects virtually every organ and tissue, with a prevalence that varies significantly among the sites involved. The role of conventional imaging, such as computed tomography and magnetic resonance imaging, in the assessment of hepatosplenic sarcoidosis is well established by revealing organ enlargement, multiple discrete nodules, and lymphadenopathy. In this review, we aim to describe contrast-enhanced ultrasound (CEUS) findings in liver and spleen involvement by sarcoidosis, reporting evidence from the literature and cases from our experience, after a brief update on safety profile, cost-effectiveness, and clinical indications of this novel technique. Furthermore, we highlight potential advantages of CEUS in assessing hepatosplenic sarcoidosis that may be useful in the clinical practice.